Function of Feline Signaling Lymphocyte Activation Molecule as a Receptor of Canine Distemper Virus - HARA, Yuka; SUZUKI, Junko; NOGUCHI, Keita; TERADA, Yutaka; SHIMODA, Hiroshi; MIZUNO, Takuya; MAEDA, Ken (Journal of Veterinary Medical Science, 2013)
Morbilliviruses use signaling lymphocyte activation molecule (SLAM) as a receptor for their entry to cells. In this study, a complete gene encoding SLAM of a domestic cat was identified. The identity of feline SLAM with canine one was 73%, and feline SLAM formed the same cluster with those of carnivores. Furthermore, feline cell expressing feline SLAM supported growth of canine distemper virus (CDV) as well as that expressing canine one. These results indicated that feline SLAM can function as a receptor for morbilliviruses, and our established feline cells that express feline SLAM might be useful for analysis of morbilliviruses originated from felids.